Dimensi Edukatif pada Kisah-Kisah Al-Qur'an - Siswayanti, Novita (SUHUF, 2010)
The stories in Qur'an are Allah’s decrees which convey more beau-tiful values beyond any religious text ever written. It is the holiest scripture and is written in a wonderful, understandable, and attract-ive language humbly conveying a vast amount of information about life and events that happened in the past. It’s aim is to be an object of reflection for human beings living in this age and the future. Even more so, the stories in Al-Qur'an also entail an educative function providing learning materials, and teaching methods, regarding the transformative power of Islam and the internalization of true religious values.